Targeting NLRP3 Inflammasome in Translational Treatment of Nervous System Diseases: An Update - Yu, Qingying; Zhao, Tingting; Liu, Molin; Cao, Duo; Li, Jiaxin; Li, Yanling; Xia, Mengyao; Wang, Xiaoyu; Zheng, Tingting; Liu, Chuanguo; Mu, Xiangyu; Sun, Peng (Frontiers in Pharmacology, 2021)
Neuroinflammatory response is the immune response mechanism of the innate immune system of the central nervous system. Both primary and secondary injury can activate neuroinflammatory response. Among them, the nucleotide-binding oligomerization domain-like receptor protein 3 (NLRP3) inflammasome plays a key role in the inflammatory response of the central system. Inflammasome is a type of pattern recognition receptor, a cytoplasmic polyprotein complex composed of members of the Nod-like receptor (NLR) family and members of the pyrin and HIN domain (PYHIN) family, which can be affected by a variety of pathogen-related molecular patterns or damage-related molecular patterns are activated. As one of the research hotspots in the field of medical research in recent years, there are increasing researches on immune function abnormalities in the onset of neurological diseases such as depression, AD, ischemic brain injury and cerebral infarction, the NLRP3 inflammasome causes the activated caspase-1 to cleave pre-interleukin-1β and pre-interleukin-18 into mature interleukin-1β and interleukin-18, in turn, a large number of inflammatory factors are produced, which participate in the occurrence and development of the above-mentioned diseases. Targeted inhibition of the activation of inflammasomes can reduce the inflammatory response, promote the survival of nerve cells, and achieve neuroprotective effects. This article reviews NLRP3 inflammasome’s role in neurological diseases and related regulatory mechanisms, which providing references for future research in this field.